Impact of health conditions on daily functioning in Kenyan populations: A scoping review - Naomi W. Kingau; Quinette A. Louw; Maria Y. Charumbira (African Journal of Disability)
Background: Kenya faces significant challenges in addressing the impact of various health conditions. Understanding the functioning problems associated with these conditions is crucial for informing targeted interventions and improving overall healthcare outcomes.